Fatores associados com a renda na exploração pecuária: estudo de uma situação na Bahia - Lapa, Armando José; Norberto Muniz, José; J Guerrero, Solon; Leitão e Silva, Josué (Revista Ceres, 2025)
The study analyzes the influence of two types of factors: ignorance and incapacity in relation to the net income of the cattle beef farmers of two municipios with different degrees of modernization in southern Bahia.